PENGEMBANGAN STRATEGI PEMASARAN PRODUK GULA TAPO (STUDI KASUS DI DESA AMBESIA KECAMATAN TOMINI KABUPATEN PARIGI MOUTONG) - Azhari, Moh Halini; Yantu, Marwan; Asih, Dewi Nur (AGROTEKBIS, 2013)
Arenga  is one of the strategic commodities that has to be developed, this plant has high economic value and  well known  to most Indonesian.  In Ambesia village,  Arenga sap is used by combining with other materials and processed traditionally, resulting  to a typical snack and commonly called Tapo Sugar. This study aimed to develop a marketing strategy for Tapo sugar product by identifying the internal and external factors that affect marketing of sugar tapo and also analyze alternative strategy for marketing tapo Sugar from Ambesia village. Results obtained with a coordinates analysis that the alternative strategy is in quadrant I, which indicates that the right strategy is the strategy of SO (Strength-Opportunity) called also an aggressive strategy, namely (i) improve the quality of the workforce through training effort that able to encourage local communities to create job, (ii) to maximize the utilization of raw material which is adequate in the village, (iii) maintain the authentic flavor of Tapo suger for attracting agro-tourism and market at national level, (iv) innovate new flavors to become an agro competitive product